Graphene oxide enhanced ionic liquid plasticisation of chitosan/alginate bionanocomposites. (1st February 2021) - Chen, Pei; Xie, Fengwei; Tang, Fengzai; McNally, Tony
Graphical abstract: Highlights: Chitosan and chitosan/alginate plasticised by glycerol or ionic liquid (IL). GO/rGO improved plasticiser distribution depending on matrix and plasticiser type. IL weakened chitosan–alginate interactions while GO counteracted this effect. For IL-added blend, surface hydrophobicity increased with GO but reduced with rGO. New routes in which GO or rGO interfere with biopolymer structure revealed. Abstract: The effect of graphene oxide (GO) or reduced GO (rGO) on the structure and properties of polyelectrolyte-complexed chitosan/alginate bionanocomposites is highly dependent on plasticiser type (glycerol or 1-ethyl-3-methylimidazolium acetate ([C2 mim][OAc])) due to the competing interactions between the components. For the glycerol-plasticised chitosan/alginate matrix, inclusion of GO/rGO enhanced the chitosan crystallinity and increased matrix ductility. While the chitosan/alginate matrix plasticised by [C2 mim][OAc] showed dramatically weakened interactions between the two biopolymers, GO was highly effective at counteracting the effect of [C2 mim][OAc] by interacting with the biopolymers and the ionic liquid ions, resulting in enhanced mechanical properties and decreased surface hydrophilicity. Compared with GO, rGO was much less effective at promoting chitosan–alginate interactions and even resulted in higher surface hydrophilicity. However, irrespective of the plasticiser type, inclusion of rGO resulted in reduced crystallinity by restricting the interactions between [C2 mim][OAc] and the biopolymers, and higher ionic conductivity.